PMO-039 Is nutritional risk associated with adverse clinical outcomes such as length of stay and mortality in spinal cord injured patients admitted to a spinal centre?. (28th May 2012) - Wong, S S H; Derry, F; Jamous, A; Harini, S; Grimble, G; Forbes, A
Abstract : Introduction: Malnutrition is common in patients with spinal cord injuries (SCI), 1 but its impact on clinical outcome may be underestimated. A disease specific nutrition screening tool (NST): the Spinal Nutrition Screening Tool (SNST) has been developed for use in patients with SCI but its predictive validity requires further investigation. 2 Methods: A multicentre (n=4), prospective, cross sectional and longitudinal study was therefore performed to evaluate whether undernutrition risk, measured using a simple validated nutrition screening tool (NST): the Spinal Nutrition Screening Tool (SNST), is associated with clinical outcomes such as the duration of in-patient stay (LOS) and 12 month mortality. Multivariate regression analysis was used. Results: One-hundred and fifty SCI patients (aged 18–88, median: 16.9, 30.7% female) were studied in four UK SCI centres (SCIC) between July 2009 and March 2010. The median LOS was 101 days (SD: 94.1) and the 12 month mortality rate was 4.7%. 44.6% were at risk of undernutrition and these individuals had a significantly longer LOS [median LOS (SD): 129 (102.1) vs 85 days (84.6); p=0.012] and greater 12-month mortality [9.2% vs 1.4%; p=0.036]. Multivariate regression identified acute admission and serum albumin level are independent predictors for long hospital LOS. Conclusion: The present study suggests that nutrition risk identified by the SNST score is associated with adverse clinical outcomes. Serum albumin is an independent predictor for an adverse clinical outcome. Nutritional screening on admission and periodic repeating may be helpful in improving clinical outcomes if it is used to influence practice. Competing interests: S Wong grant/research support from: Abbott Nutrition, F Derry: None declared, A Jamous: None declared, S Harini: None declared, G Grimble: None declared, A Forbes: None declared. References: 1. Wong S, et al. Br J Nutr 2011. doi:10.1017/S0007114511006234 2. Wong S, et al. Eur J Clin Nutr 2011. doi:10.1038/ejcn.2011.209